Basic Needs as the Foundation of Consumer Behavior: An Analytical Study of Al-Ghazali's Thought - Bin Lahuri, Setiawan; Nurkholifah, Euis; Zarkasyi, M. Ridlo; Ramdani Harahap, Soritua Ahmad (IAIN Syekh Nurjati Cirebon, 2024)
Consumer behavior that has a lot of consumptive tendencies makes this pattern incompatible with consumption in the Islamic economics. Society has the ideology of consuming excessively, unknowingly, and sustainably. Purchases of goods are only based on desires and do not consider needs, so it is necessary to enforce consumption patterns so that they do not fall into the excessive category. The research methodology used is a literature study method by conducting an in-depth reading analysis of various references related to consumer behavior, especially examining various existing literature works. Researchers reviewed several books written by Al Ghazali and several related figures to obtain additional analysis in this research. The results of this research indicate that the consumption theory according to Al Ghazali is not only oriented to satisfaction. Consumption in Islam is more to make people more obedient in worship. Humans are not required to meet their needs sporadically but must comply with sharia principles. Other important things by paying attention to halal, good and mashlahah for the goods they consume. Â Keywords: Consumer behavior, Islamic Economics, Society, Al-Ghazali